Empires - Doyle, Michael, 1948- (Ithaca, New York : Cornell University Press, 1986)
"The analysis of the causes and patterns of imperialism has long been a difficult academic exercise. ... To structure this far-ranging phenomenon and arrange its course in a concise, interpretive essay takes pluck, if a good adjective from the derring-do novels of empire may be used here. Michael W. Doyle had that pluck and has succeeded remarkably well in his task. This is a splendid essay, an effective combination of broad historical analysis and well-presented theoretical assessments derived from the social sciences. The book will no doubt stand as one of the best contemporary syntheses of the progress of imperialism. ... Doyle has read widely and well. He has mastered his material and has done with it something masterly: he has made the whole more than the sum of the parts. What follows next from the lively mind of this scholar will be pleasantly anticipated."--American Historical Review.
Imperialism and empire -- Introduction -- Athens and Sparta : empire and hegemony -- Rome -- The Ottoman, Spanish, and English empires -- The sociology of empires : hypotheses -- Introduction to Part 2 -- Tribal peripheries and formal empire -- Patrimonal peripheries and informal empire -- The international system and nineteenth-century imperialism -- Greater Britain -- France, Germany, and Spain -- The politics of nineenth-century imperialism -- Imperial development : the end of empire?
Includes bibliographical references (pages 373-398) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: Imperialism; Imperialism -- History; Impérialisme.; Impérialisme -- Histoire; HISTORY -- World; Imperialism; Imperialismus; Geschichte; Afrika; Imperialisme; Imperialismo; Empire; Histoire; Impérialisme.; Geschichte 1800-1900; History